2007
DOI: 10.1128/iai.01290-06
|View full text |Cite
|
Sign up to set email alerts
|

The Combined CTA1-DD/ISCOMs Vector Is an Effective Intranasal Adjuvant for Boosting PriorMycobacterium bovisBCG Immunity toMycobacterium tuberculosis

Abstract: Infection with Mycobacterium tuberculosis, the causative agent of tuberculosis (TB), remains one of the leading causes of mortality worldwide. The current "gold standard" vaccine Mycobacterium bovis BCG has a limited efficacy that wanes over time. The development of a vaccine to boost BCG-induced immunity is therefore a highly active area of research. Mucosal administration of vaccines is believed to provide better protection against pathogens, such as M. tuberculosis, that invade the host via mucosal surfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 40 publications
(38 reference statements)
0
45
0
Order By: Relevance
“…These results suggest that to improve the oral efficacy of ISCOMs a modification of the immunization protocol such as including an oral/injectable prime-boost regimen or the use of additional coatings or adjuvants may improve efficacy. The inclusion of the mucosal adjuvant CTA1-DD did enhance the ability of nasally delivered ISCOMs to enhance immune responses [164], suggesting that the addition of an additional immune stimulatory component may serve to potentiate the oral efficacy of ISCOMs.…”
Section: Immune-stimulating Complexesmentioning
confidence: 99%
“…These results suggest that to improve the oral efficacy of ISCOMs a modification of the immunization protocol such as including an oral/injectable prime-boost regimen or the use of additional coatings or adjuvants may improve efficacy. The inclusion of the mucosal adjuvant CTA1-DD did enhance the ability of nasally delivered ISCOMs to enhance immune responses [164], suggesting that the addition of an additional immune stimulatory component may serve to potentiate the oral efficacy of ISCOMs.…”
Section: Immune-stimulating Complexesmentioning
confidence: 99%
“…A recent study showed that i.n. administration of the antigenic fusion protein Ag85B-EAST-6 mixed with the mucosal combined adjuvant vector CTA1-DD/ISCOM could significantly boost IFN-␥-secreting CD4 ϩ T cells in the lung elicited by prior BCG immunization and improved protection against M. tuberculosis challenge (25).…”
Section: The Live Attenuated Bacillus Calmette-guérin (Bcg) Vaccine Amentioning
confidence: 99%
“…A novel, effective vaccination strategy against adult pulmonary TB has therefore become an international research priority. Nasal TB vaccines have been shown to be capable of inducing both local and systemic responses and to confer protection from infection (1,2,7,10,15,17,20,30,48,52,57). The exact correlates of protection against TB are not yet fully understood; however, CD4 ϩ and CD8 ϩ T cells have been shown to play a crucial role in conferring protection from M. tuberculosis infection (2, 53).…”
Section: The Primary Activation Of T-helper and T-cytotoxic Cells Folmentioning
confidence: 99%